SOYBEAN PESTS AND THEIR TROPHIC RELATIONSHIPS IN THE CONDITIONS OF CENTRAL FERGANA - Gafurova Ominakhan Muhammadzikirovna; Aminjonova Gulasal Fakhriddin's daughter (Journals Park Publishing, 2022)
This article provides information on the morphological structure, pests and their trophic relationships of soybeans grown in the conditions of Central Fergana.
Keywords: credit hour, credit module, independent study, abstract, essay, non-standard test.